On the clone selection, ectomycorrhizal inoculation of short-rotation willows (Salix spp.) and on the effects of some nutrients sources on soil properties and plant nutrition - Lumme, Ilari (1989)
Approx. 300 willow clones were tested in a field trial carried out in a mined peat area. Clones with high survival, high leafless, above-ground biomass production and with proper growth habit and sprouting capacity were selected from among the southern willow varieties, such as Salix viminalis L. and S. Schwerinii Wolf, but the winter hardiness of these clones was poor. The local Salix myrsinifolia Salisb. species included winterhardy clones; these local clones also showed marked variation in biomass production. The effects of ectomycorrhizal inoculation on the growth of two southern fast-growing willow species were tested. Most of the inoculants were able to form ectomycorrhiza with willow clones tested and an Entoloma sp. inoculant and some Hebeloma crustuliniforme inoculants even increased the biomass production of the clones, apparently due to symbiotic effects in a mined peat soil. The latter result, however, was inconsistent, nor did the inoculants substitute for phosphorus fertilization, but acted synergistically instead. Except for apatites all the tested nutrient sources containing P may be used to increase the exceptionally low available P content of mined peat soils. The conifer bark ash tested, however, caused the most balanced effect in soil chemistry as it also increased the soil K content. The limestone stabilized domestic sewage sludge increased the soil N and P content and enhanced the soil microbiological activity, but the K content was too low and Fe content was obviously too high. High peat ash dosage, 50 t/ha, increased the soil P and Mg contents, promoted the soil microbiological activity and enhanced nitrogen cycle of the soil. The K content of the peat ash was low, however. Biotite may be a suitable slow-release K source to be used in addition with peat ash in mined peat soils.